(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article will focus on the process of formation of the spiritual space in the New Uzbekistan, its content and development trends. The emergence of the phenomenon of the new Uzbekistan and its impact on the world economy have been analyzed.